2007
DOI: 10.1111/j.1574-6941.2006.00262.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing bacterial dynamics along a transect from supraglacial runoff to proglacial lakes of a high Arctic glacieri

Abstract: Bacterial production in glacial runoff and aquatic habitats along a c. 500 m transect from the ablation area of a Svalbard glacier (Midre Lovénbreen, 791N, 121E) down to a series of proglacial lakes in its forefield were assessed. In addition, a series of in situ experiments were conducted to test how different nutrient sources (glacial flour and dissolved organic matter derived from goose faeces) and temperature affect bacterial abundance and production in these ecosystems. Bacterial abundance and production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
66
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(72 citation statements)
references
References 47 publications
6
66
0
Order By: Relevance
“…The concentration of SRP detected in the supraglacial channel water on Werenskioldbreen ranged from \0.5 to 2.9 lg l -1 , and in cryoconite holes from \0.5-2.3 lg l -1 (Table 2). These values are similar to those found in glacial runoff (0.9-1.0 lg l -1 ; Mindl et al 2007) and cryoconite holes (0.9-9.0 lg l -1 ; Säwström et al 2002) on another Svalbard glacier (Midtre Lovénb-reen) or in cryoconites on the White Glacier in the Canadian High Arctic (0.6-13.5 lg l -1 ; Mueller and Pollard 2004). The low concentrations measured during this study were probably caused by several factors.…”
Section: Dissolved P In Supraglacial Watersupporting
confidence: 88%
“…The concentration of SRP detected in the supraglacial channel water on Werenskioldbreen ranged from \0.5 to 2.9 lg l -1 , and in cryoconite holes from \0.5-2.3 lg l -1 (Table 2). These values are similar to those found in glacial runoff (0.9-1.0 lg l -1 ; Mindl et al 2007) and cryoconite holes (0.9-9.0 lg l -1 ; Säwström et al 2002) on another Svalbard glacier (Midtre Lovénb-reen) or in cryoconites on the White Glacier in the Canadian High Arctic (0.6-13.5 lg l -1 ; Mueller and Pollard 2004). The low concentrations measured during this study were probably caused by several factors.…”
Section: Dissolved P In Supraglacial Watersupporting
confidence: 88%
“…Moreover, most of these studies have been performed in one single habitat. However, a few studies have examined multiple habitats678, including glacial runoff and aquatic habitats. These studies have shown that different habitats harbour different microbial communities and biodiversity, albeit with some common groups, even within the same glacier.…”
mentioning
confidence: 99%
“…Nutrient fluxes from various sources, i.e. aeolian and guano inputs (60, 61), glacial flour particle release (39), and the transport of entrapped organic and inorganic compounds through cryoconite holes (61), influence in a complex matter biogeochemical cycles as well as the size and structure of microbial communities in the Arctic cryosphere (50). Interactions between ice-covered land and marine ecosystems (25), and freshwater from retreating glaciers (21, 62) also contribute to the Arctic microbial food web.…”
mentioning
confidence: 99%
“…The fjords and archipelago of Svalbard have recently attracted attention for assessing the impact of anthropogenic activities and global warming on the microbial ecology of the European part of the Arctic (20, 39, 57, 61). Microbial communities and glacial run-off to ice lakes have been extensively examined; however, information on the structures of microbial communities in the southern part of the Spitsbergen/Svalbard island complex is limited.…”
mentioning
confidence: 99%